MODERN TRENDS IN MEDICAL THERAPY OF CHRONIC GENERALIZED PARODONTITIS - M. V. Dudar; L. S. Vasilyeva; V. D. Molokov (Acta Biomedica Scientifica, 2016)
The review deals with the analysis of modern methods of treatment of chronic generalized parodontitis from the perspective of differentiated principle of treatment of this disease. Particular attention is paid to methods of medical treatment, their diversity on the efficiency and mechanisms of therapeutic effects to select appropriate treatment, taking into account all the individual characteristics of the patient, aetiology, pathogenesis and severity of chronic generalized parodontitis. It has been demonstrated that an important aspect to achieve high efficiency of treatment is a method of drug delivery. The most effective method is a transmembrane dialysis, which makes it possible simultaneously to obtain the maximum concentration of the therapeutic substances in the inflammatory focus and to eliminate from the inflammatory focus the low-medium weight tissue decomposition products, products of metabolism, while maintaining factors of regeneration and protection against infection. It has been evinced the advantages of sanogenetic therapy using vitamin cocktail and some higher plants BAS containing terpenoids (bornylacetate and its semisynthetic stereoisomer - isobornyl acetate), as the least toxic, having analgesic and anti-bacterial properties comparable with antibiotics, and capable to stimulate repair processes. The good water solubility of these substances provides ample possibility of using these drugs in the form of solutions for rinsing, transmembrane dialysis, as liquid at ultrasonic curettage.